Students’ Beliefs on Learner Autonomy in English Language Classroom - Jora, Man Bahadur (Journal of NELTA Gandaki, 2020)
This study tries to explore the students' beliefs on learner autonomy in English language class at the secondary level. I, as a researcher, collected first hand data from the students of secondary level of government aided school. The students of school A are interpreted on the basis of ethnographic research. This study analyses students’ beliefs and reflections on learner autonomy. Moreover, the present study relates and connects two theories in the process of developing and shaping of it. It emphasizes the students’ perceptions toward learning autonomy and the researcher has anticipated mentioning the students’ perceptions on English language teaching learning in the government aided schools. The findings of this study reveal that learner autonomy is necessary for the learners' encouragement, the opportunity of learning language and learner’s development, and for responsibility of the learners.